LIFE SKILL EDUCATIONAL MANAGEMENT MODEL FOR THE SOCIAL SKILLS OF CHILDREN WITH SPECIAL NEEDS - Ningsih, Tri Ratna; Asnar Firoj Mu’thasim, Asnar; Meri Pramaisila Trisilo, Meri; Agnes Ovitarika, Dice (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Teaching life skills to children with special needs is not as easy as normal children. This research aims to determine the influence of the life skills model on the social closeness of children with special needs. The population was 37 students with a sample of 20 treatment groups and 17 control groups. This research used female respondents as SLBS PGRI Dlanggu Mojokerto students. This research is a type of quantitative research with a research design using a quasi-experiment with a pre-test and post-test control group approach. using the Wilcoxon range test statistical test. The research result is ρ 0.000, meaning it is smaller than α 0.05, H0 is rejected, meaning there is a difference between the treatment group and the control group. The life skills model has a big influence on the socialization of children with special needs. The Life Skills model with intense assistance from teachers will influence good habits in students and influence socialization with school friends and the environment.